Pelayanan Misi bagi Anak di Era Digital: Sebuah Pemetaan Urgensitas - Yulius Wijaya; Aji Suseno (Sekolah Tinggi Teologi Baptis, Jakarta, 2023)
In evangelizing, we need to pay attention to who we will evangelize and what factors influence, such as mindset, culture, and habits and characters. Today, evangelism has its challenges in evangelizing the generation of children who live in the Industrial Revolution 4.0 and 5.0 era with all the increasingly sophisticated technological developments. If the methods and ways of evangelism still use traditional forms, then the current generation of children will need to understand the salvation carried out by evangelists. This research uses a qualitative description approach by examining library sources. This research aims to find the urgency of finding the principles of effective evangelism to children, namely the doctrine of the Bible and salvation, which must still be the main part for children, as well as the creativity and integrity of the evangelist. While the content principles of effective evangelism relevant to children in the digital age are following Jesus, the best